Implementation Strategy of the Mutanaqishah Musyarakah Academic at Home Ownership Financing in Sharia Banks in Indonesia - Tuti Anggraini; M. Yasir Nasution; Andri Soemitra (Budapest International Research and Critics University, 2021)
This research aims to: (1) Knowing the obstacles faced in implementing the Mutanaqisah Musharaka Financing (2) The solutions taken to overcome these obstacles; and (3) the right strategy to apply musyarakah mutanaqisah financing. This study uses the Analytic Network Process (ANP) method and the assistance of Super Decision software. ANP is carried out in three stages, namely: first, in-depth interviews with Islamic banking experts and practitioners to identify the factors that influence the minimum amount of musyarakah mutanaqisah. Second, the results of the first step are used to create an ANP framework and a questionnaire addressed to Islamic banking experts and practitioners; and third, ANP analysis to determine the best priorities, solutions and strategies for implementing Musyarakah mutanaqisah financing in Islamic banking.The results showed that: (1) The constraints faced by Islamic banking in implementing Musyarakah Mutanaqisah financing for Islamic banking KPRS financing can be divided into two, namely internal and external problems. Internal problems stem from internal banking, banking human resources, and musyarakah mutanaqisah financing products. External problems originate from customers, authorities, and Islamic banks. The most priority problem faced is internal problems, namely human resources (HR) associated with low knowledge and skills about the MMQ contract. Meanwhile, the most dominant external problem is Islamic banking with a lack of insight into the MMQ contract. (2) The solutions given in determining the financing strategy for the musyarakah mutanaqisah are divided into two, namely internal and external solutions. The most priority solution comes from internal solutions, namely product solutions in the form of Islamic banking that must vary the contract, especially for the MMQ contract; and (3) The alternative with the most priority in determining the financing implementation strategy with the musyarakah mutanaqisah contract in Islamic banking is the Socialization and Education Program, followed by Contract Optimization, Portfolio Development, Image Strengthening, MMQ Segmentation Mapping, and MMQ financing market segmentation.